PENGARUH PENGGUNAAN TEKNOLOGI INFORMASI, MOTIVASI KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA GURU SMA NEGERI 82 JAKARTA SELAMA MASA PANDEMI COVID-19 - Mutiara Sari Pratiwi (2021)
This study is a quantitative study that aims to determine the effect of the use of information technology, work motivation, and job satisfaction on the performance of teachers at SMA Negeri 82 Jakarta. The population in this study were PNS teachers at SMA Negeri 82 Jakarta. The number of samples used in this study were 34 employees which were the entire population. The data used in this study is primary data, namely by distributing questionnaires to PNS teachers. The data analysis technique used in this research is quantitative data analysis technique using statistical methods. The statistical method used is Partial Least Square (PLS). The test results (1) the use of information technology has a positive and significant effect on teacher performance at SMA Negeri 82 Jakarta, (2) work motivation has a positive and significant effect on teacher performance at SMA Negeri 82 Jakarta, (3) job satisfaction has a positive and significant effect on teacher performance at SMA Negeri 82 Jakarta.